Perceived stress, coping strategies, symptoms severity and function status among carpal tunnel syndrome patients: a nurse-led correlational Study - Maha Gamal Ramadan Asal; Mohamed Hussein Ramadan Atta; Sally Mohammed Farghaly Abdelaliem; Ahmed Abdelwahab Ibrahim El-Sayed; Hoda Abdou Abd El-Mo (BMC, 2024)
Abstract Background Carpal tunnel syndrome (CTS) is a prevalent condition characterized by hand pain, tingling, and numbness. The severity of symptoms and functional status in CTS patients may be influenced by perceived stress and how individuals cope with it. However, scarce knowledge exists about the role of coping strategies as moderators in this relationship. Unfolding the role of perceived stress and coping strategies for CTS management will help the nurse to provide comprehensive and tailored nursing care. This will ultimately improve patient comfort, functionality, and quality of life. Purposes This study aimed to examine the role of coping strategies (adaptive and maladaptive) in the relationship between perceived stress and both symptoms severity and function status among those patients. Method We employed a multisite, correlational study design with moderation analysis. The study included 215 patients with CTS from neurosurgery outpatient clinics at three hospitals in Egypt. After obtaining their consent to participate, eligible participants completed anonymous, self-reported measures of perceived stress, the brief COPE inventory, and the Boston Carpal Tunnel Questionnaire. Demographic and biomedical data were also collected. The questionnaire took about 20 min to be completed. The data was collected over six months, starting in February 2023. Results The results showed that perceived stress, adaptive coping, and maladaptive coping were significant predictors of symptoms severity and functional status. Adaptive coping moderated the relationships between perceived stress and both symptoms severity and function status, while maladaptive coping did not. The interaction between perceived stress and adaptive coping explained a moderate effect on symptoms severity and function status after controlling for the main effects and the covariates. Conclusion This study explored the relationship between perceived stress, coping strategies, and outcomes in patients with CTS. The results indicate that nurses play a vital role in assessing and assisting patients to adopt effective coping strategies to manage perceived stress and alleviate symptoms and functional impairment. Moreover, the findings support the need for psychological interventions that address both perceived stress and coping strategies as a way to enhance the functioning status and quality of life of patients with CTS.